La chiusura degli ospedali psichiatrici giudiziari: aspetti normativi e storici - Fargnoli, Domenico (Il sogno della farfalla, 2019)
In the Italian psychiatric legislation, the idea of “apparent social dangerousness” regarding mentally ill patients has been completely overcome by law 180 (1978), which ceased to mention dangerousness as a reason for psychiatric hospitalization. Subsequently, the concept of dangerousness in mentally ill people is no longer mentioned in the Italian psychiatric legislation, surviving only in penal laws. Judgement on the social danger of the mentally ill should be undoubtedly affirmed in the legal field: forensic psychiatry has greatly and authoritatively claimed and concluded that it is indeed fundamental to overcome the misleading, reductive and non-scientific concept of “socially dangerous”. While rejecting this latter concept, as expression of a custody approach, it cannot be denied that a connection between mental illness and criminal action can indeed be found in the limited field of diagnostic and clinical evaluation as historically demonstrated by the Miklus’s case which determined the end of the experience sought by Franco Basaglia in Gorizia.